Nazi-organized recreation and entertainment in the Third Reich - Timpe, Julia (The Holocaust and its contexts, 2017)
"This book explores the activities of the Nazi regimes vast leisure programme. Shortly after coming to power in Germany, it began a large-scale undertaking to bring happiness and a good life to so-called Aryan Germans, carried out by the Nazi leisure organization Kraft durch Freude. Julia Timpe traces Kraft durch Freudes practices and propaganda from 1933 through the Second World War, and analyses Nazi-organized sports classes, entertainment events, and beautification campaigns for industrial sites and the countryside, as well as Kraft durch Freudes activities in entertaining German soldiers and concentration camp guards. Contributing to newer scholarship which focuses on the integratory force of the Nazi promise of a unified racial community of all Aryan Germans, this book highlights that Kraft durch Freudes everyday production of joy was central to Nazism, closely connected to the destructive side of the Third Reich, and ultimately a major reason for Nazisms success among the German population" --